Small diatoms (Bacillariophyta) in cultures from the Styx River, New Zealand, including descriptions of three new species - Novis, Phil M.; Braidwood, Jasmine; Kilroy, Cathy (Phytotaxa, 2012)
We obtained morphological and molecular data for 12 strains of small culturable diatoms from the Styx River, a semi-urban catchment in Christchurch, New Zealand, associated with high nutrient levels and increasing development pressure. Sellaphora styxii, Planothidium victori, and Eolimna krummensis are described as new to science, and material referable to the Nitzschia palea complex is genetically distinctive and would represent a new species if the genus was revised. E. krummensis had already been sequenced (but not described or named) from Europe. The other strains, Planothidium frequentissimum, Gomphonema parvulum, Fistulifera saprophila, Navicula cryptocephala, N. veneta, Craticula molestiformis, and Cyclotella meneghiniana are well known from the Northern Hemisphere; thus 3 of the 12 strains are presently known only from New Zealand. It is difficult to evaluate the likelihood of their endemism, but we expect that they will ultimately be found to be cosmopolitan. Infraspecific distribution patterns could be evaluated with molecular data, but would require the widespread sequencing of more variable gene regions.